Oil spill governance on the development of seven fishing ports in Indonesia fishing management area - Budhi Gunadharma Gautama; Penny Dyah Kusumaningrum; Vivi Yovita; Anwar Rizal (BIO Web of Conferences, 2023)
Indonesia marine ecosystem has a serious threat coming from oil spill. The unintentional spill has low probability but give high consequences, meanwhile the intentional spill has high probability with low consequences. The negative impact of oil spill may affect not only the environment but also the human life from social and economic aspects. The Ministry of Marine and Fisheries is the government authority that responsible for the management of marine and fisheries resources based on the sustainable development. Fisheries as the key activities in coastal areas can generate local economic growth by numbers of activities on Fishing Ports. This research is working on the observation of the oil spill in Indonesia and management of the oil spill on the 7 fishing ports in Indonesia Fishing Management Area. 6 Fishing Ports are located on the North of Java and 1 is located on the South of Java. We identified and quantified the potential source of the oil spill and the recommendation with its mitigation planning. The analysis showed that the Fishing Ports in FMA 712 has more threat of oil spill than those in FMA 573. Nizam Zaman fishing port was the most potentially oil polluted meanwhile the least was Cikidang.